2022
DOI: 10.2147/ijgm.s367173
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Necroptosis-Related Prognostic Index and Associated Regulatory Axis in Kidney Renal Clear Cell Carcinoma

Abstract: Background Kidney renal clear cell carcinoma (KIRC) is one of the most common aggressive malignancies in the genitourinary system with the high degree of immune infiltration. However, the role of necroptosis-related genes in the immune infiltration of KIRC and the impact on overall survival have not been adequately studied. Methods Differentially expressed necroptosis-related genes were identified based on The Cancer Genome Atlas (TCGA). Then, we constructed a necroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Kidney renal clear cell carcinoma (KIRC) is the most common histological subtype of renal cell carcinoma, accounting for 80–90% of all cases, with a high degree of immune infiltration [ 1 , 2 , 3 ]. A better understanding of the immune system and a discovery that tumors can take advantage of immune checkpoints to promote their survival and growth have resulted in the creation of immune checkpoint inhibitors (ICIs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidney renal clear cell carcinoma (KIRC) is the most common histological subtype of renal cell carcinoma, accounting for 80–90% of all cases, with a high degree of immune infiltration [ 1 , 2 , 3 ]. A better understanding of the immune system and a discovery that tumors can take advantage of immune checkpoints to promote their survival and growth have resulted in the creation of immune checkpoint inhibitors (ICIs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are three studies reporting necroptosis-related genes in KIRC [ 49 51 ], however, these three articles only roughly described the necroptosis-related genes level in RCC. We enriched these necroptosis-related genes and found that these necroptosis-related genes may be related to immunity in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that necroptosis-related genes are promising biomarkers for predicting prognosis and treatment response in ccRCC ( Luo and Zhang, 2022 ). Necroptosis-related signatures have also been demonstrated as novel prognostic predictors of immune microenvironment and treatment response in ccRCC ( Chen et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%